LEARNING OUTCOMES OF THE SENIOR HIGH SCHOOL STUDENTS OF GHANA IN CORE MATHEMATICS: AN ANALYTICAL STUDY - Francis Ennin; Karanam Pushpanadham (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study examines and analyses the Core Mathematics learning outcomes of Senior High School students in Ghana. Data was downloaded online from the West African Examination Council (WAEC) website. The data consisted of published provisional WASSCE Core Mathematics results for 2017 to 2022. The data were analysed using descriptive statistics (Frequencies and percentages). Graphs were used for clarity of the analyses. It was realised that, though there has been an improvement in the results of candidates in recent years, many students still fail to achieve the necessary grades for tertiary education admission. It was also revealed that the improvement in the results of candidates in recent times might stem from malpractices on the part of schools and students during the examination.